The involvement of arbuscular mycorrhizal fungi in modulating polyamine metabolism and low-temperature tolerance enhancement in white clover - Yao, Songyuan; Li, Lin; Xiong, Haitang; Zhang, Peng; Ju, Tingting; Chen, Zhiwei; Zheng, Lanlan (Frontiers in Plant Science, 2025)
Sustained low temperatures can prevent white clover (Trifolium repens L.) from overwintering and regreening, making it difficult to revive the plants in the spring. Arbuscular mycorrhizal fungi (AMF) are widely known for their ability to enhance host stress tolerance. It is unclear whether AMF can enhance the low-temperature tolerance of white clover, which is associated with polyamines. The purpose of this study was to examine how inoculating white clover with an arbuscular mycorrhizal fungus Funneliformis mosseae affected the biomass, leaf chlorophyll and gas exchange, levels of root polyamines (putrescine, spermidine, and spermine), activities of key polyamine-related enzymes, and the expression level of the S-adenosyl-L-methionine decarboxylase (TrSAMDC1) gene at low temperatures (4°C for four days). The low-temperature treatment inhibited the root mycorrhizal colonization rate. Mycorrhizal inoculation significantly increased shoot, root, and total biomass, with greater increases found at optimal temperatures (22°C/18°C, 16 h/8 h, day/night temperature) than at low temperatures. Similarly, AMF inoculation significantly improved leaf gas exchange parameters, with larger increases observed at optimal temperatures than at low temperatures. Low temperatures caused a considerable increase in putrescine and spermidine levels, while simultaneously decreasing spermine levels. Mycorrhizal inoculation elevated putrescine, spermidine, and spermine levels regardless of temperature conditions, along with a significant rise in the (spermidine+spermine)/putrescine ratio. Mycorrhizal plants also exhibited considerably increased activities of arginine decarboxylase and polyamine oxidase, but not ornithine decarboxylase, in response to low temperatures. Mycorrhizal inoculation, together with low temperatures, elevated TrSAMDC1 expression. The observed alterations in mycorrhiza-mediated polyamines were primarily attributed to increased arginine decarboxylase activity and TrSAMDC1 expression. This study demonstrated the role of mycorrhizal fungi in modulating polyamine metabolism and enhancing plant tolerance to low-temperature stress.